Entre Pluralismo e Populismo. Democracia, Migração e Estado Social aos olhos dos portugueses - Fernandes, T. (Entre Pluralismo e Populismo. Democracia, Migração e Estado Social aos olhos dos portugueses, 2024)
National Survey